ETL DATA WAREHOUSE ON PERFORMANCE MEASUREMENT - Linda Sutriani; Indra Yatini Buryadi; Hera Wasiati; Sudarmanto Sudarmanto (Journal of Intelligent Software Systems, 2023)
Measuring the organizational performance correctly will turn out accurate data which can be analyzed to provide important information for management in making decisions to improve company performance. This is because in the past, the performance appraisal was only based on financial measures. However, the editor-in-chief needs more than just financial indicators to improve performance. The Balanced Scorecard measures four organizational dimensions, such as customer, financial, internal business, and learning and growth. Although originally designed for the private sector, many public organizations apply it as modifications to suit their needs. The Balanced Scorecard is an effective method for measuring and achieving organizational performance. This research involves ETL in the Balanced Scorecard process to combine data from various sources into a large central repository called a data warehouse